OPTIMASI DAN PEMODELAN PRODUKSI MISELIUM JAMUR SCLEROTIUM ROLFSII DENGAN PERLAKUAN FITOHORMON DAN SUMBER NUTRIEN - Aji Pangestu, Ismail
Sclerotium rolfsii is a fungal species that has a lot of potentials, for examples as a source of protein, beta glucan, and lectin. To get these benefits requires stages of mycelium biomass production. To increase mycelium growth, several attempts have been made, but the use of phytohormone is still rarely applied. This research aims to optimize mycelial growth of S. rolfsii are accomplished by providing a fitohormones and variety of nutrients variables. Approach of response surface methodology (RSM) was used to evaluate interaction between these variables toward response of S. rolfsii mycelial production. The research began by determining the effects of giving Indol-3-acetic acid (IAA), 2,4-dichlorophenoxyacetic acid (2,4 D), and 6-benzylaminopurin (BAP), (ppm; 10,50,100), and selecting one fitohormon which gives the best growth enhancing effect. Five variables are carbon source (g·L-1; 8,15,22); nitrogen source (%(v/v), 5,10); initial pH of medium (4,6,8); incubation time (days; 4,5,6); and phytohormone (ppm; 10,30), determined its relationship toward S. rolfsii mycelial production using RSM approach. Finally, a second order equation model was obtained which is then used to find the optimum response areas where production of S. rolfsii mycelium maximal. Giving phytohormon 10 and 50 ppm of IAA, and 10 ppm 2.4 D increases S. rolfsii mycelial growth but otherwise giving 50 ppm and 100 ppm of 2.4 D, and 100 ppm IAA decrease S. rolfsii mycelial growth. Giving phytohormon BAP did not significantly affect growth of S. rolfsii. Giving 10 ppm IAA is the best increasing S. rolfsii growth, up to 0.6 cm. The amount of carbon source, initial pH of the medium, and incubation time had a significant effect on S. rolfsii mycelial production while the amount of nitrogen sources and phytohormone concentrations had not significant effect. A combination of 22 g·L-1 carbon source, 6.10 initial pH medium, and 6 days incubation time optimum to produce S. rolfsii mycelium maximally. In addition, the mycelial growth of S. rolfsii good both at 5%(v/v) nitrogen source and 10 ppm phytohormones IAA. Using this approach a 12 g·L-1 dry weight of S. rolfsii mycelial is produced and two folds before optimization. In addition, this equation model can be used to predict carbon sources, initial pH of medium and incubation time requirement according to the amount of biomass to be produced.